Laboratory test and simulation for anchoring slope of steel tube foam concrete frame beam - Li, Feng; Lian, Wenjing; Hu, Yuzhong; Lan, Tian; Xiao, Tingsong (Frontiers in Materials, 2026)
The anchor frame beams have been widely applied in slope engineering. Using conventional concrete frame beams, their structure is heavy and during the installation process, a large amount of construction machinery and manpower are usually required. However, foam concrete reduces weight but has low strength. To address these issues, steel pipe foam concrete with hydrogen peroxide as the foaming agent was selected to replace the conventional concrete. Through experiments, the addition method of hydrogen peroxide, the mix ratio, and the thickness of the steel pipe were determined. Through finite element analysis of a typical cutting slope, the internal force distribution of the structure and the influence of parameters were obtained. The results show that the foam concrete sample prepared by the hydrogen peroxide solution addition method is better. The strength of 2 mm steel pipe-based steel foam concrete with a 5% hydrogen peroxide content is equivalent to that of C30 concrete, and its density is approximately 30% lower. Simultaneously, the peak moment of the articulated frame beam becomes smaller due to the presence of the hinge, but the shear force is basically unchanged. The optimal length of hinge interval in the articulated frame beam is 1.6m, and the breath and height of the beam are 0.4m and 0.5 m.